Thirty years of amphibian surveys in the Ukagurus Mountains of Tanzania reveal new species, yet others are in decline. Issue 2 (28th October 2022) - Liedtke, H Christoph; Lyakurwa, John V; Lawson, Lucinda P; Menegon, Michele; Garrido-Priego, Marina; Mariaux, Jean; Ngalason, Wilirk; Channing, Alan; Owen, Nisha R; Bittencourt-Silva, Gabriela B; Wilkinson, Mark; Larson, Joanna G; et al.
ABSTRACT: Records of biodiversity over time are important resources for assessing conservation priorities. However, such baseline data are missing for regions of key biodiversity importance. The Eastern Arc Mountains of Tanzania are known for their species richness and endemism, but not all mountain blocks have received the same attention. The Ukaguru Mountains, for example, have only infrequently been surveyed by herpetologists, with the first known herpetological survey in 1990. Here we compile and quantify all amphibian survey efforts in the Ukaguru Mountains in the past 30 years, publish an updated species list and comment on the health of amphibian populations and their habitat. We report on fourteen described species of amphibians, with potentially three additional species awaiting formal description. Of these seventeen lineages, seven are endemic to the Ukaguru Mountains. Although total species numbers remain low, compared with other Eastern Arc Mountains, surveys frequently recorded new species for the Ukaguru Mountains and for science. Worryingly, however, endemics, such as the monotypic bufonid Churamiti maridadi, have not been recorded in the past fifteen years. Our analyses show the region is becoming warmer and drier and is experiencing an alarming rate of deforestation. We find that over the past 30 years, dense forest cover inside the boundaries of the forest reserves has reduced by 8.4%.